Impact of mepolizumab in patients with high-burden severe asthma within a managed care population. (3rd April 2023) - Lugogo, Njira L.; Bogart, Michael; Corbridge, Thomas; Packnett, Elizabeth R.; Wu, Joanne; Hahn, Beth
Abstract: Objective: To evaluate the real-world impact of mepolizumab on the incidence of asthma exacerbations, oral corticosteroid (OCS) use and asthma exacerbation-related costs in patients with high-burden severe asthma. Methods: This was a retrospective study of the MarketScan Commercial and Medicare Databases in patients with high-burden severe asthma (≥80th percentile of total healthcare expenditure and/or significant comorbidity burden). Patients were ≥12 years of age upon mepolizumab initiation (index date November 1, 2015–December 31, 2018) and had ≥2 mepolizumab administrations during the 6 months post-index. Asthma exacerbation frequency (primary outcome), use of OCS (secondary outcome), and asthma exacerbation-related costs (exploratory outcome) were assessed during the 12 months pre-index (baseline) and post-index (follow-up). Results: In total, 281 patients were analyzed. Mepolizumab significantly reduced the proportion of patients with any asthma exacerbation ( P < 0.001) or exacerbations requiring hospitalization ( P = 0.004) in the follow-up versus baseline period. The mean number of exacerbations decreased from 2.5 to 1.5 events/patient/year (relative reduction: 40.0%; P < 0.001). The proportion of patients with ≥1 OCS claim also decreased significantly from 94.0% to 81.9% (relative reduction: 12.9%; P < 0.001), corresponding to a decrease from 6.6 to 4.7 claims/person/year ( P < 0.001). Of the 264 patients with ≥1 OCS claim during baseline, 191 (72.3%) showed a decrease in mean daily OCS use by ≥50% in 117 patients (61.3%). Total asthma exacerbation-related costs were significantly lower after mepolizumab was initiated ( P < 0.001). Conclusions: Mepolizumab reduced exacerbation frequency, OCS use and asthma exacerbation-related costs in patients with high-cost severe asthma. Mepolizumab provides real-world benefits to patients, healthcare systems and payers.